Crystalline morphology formation in phase-field simulations of binary mixtures - Siber, Maxime; Ronsin, Olivier J.J.; Harting, Jens (Journal of Materials Chemistry C, 2023)
Understanding the morphology formation process of solution-cast photoactive layers (PALs) is crucial to derive design rules for optimized and reliable third-generation solar cell fabrication. For this purpose, a Phase-Field (PF) computational framework dedicated to the simulation of PAL processing has recently been developed. In this study focused on non-evaporating, crystallizing binary mixtures, distinct crystalline morphology formation pathways are characterized by a systematic exploration of the model's parameter space. It is identified how, depending on material properties, regular, dilution-enhanced, diffusion-limited and demixing-assisted crystallization can take place, and which associated structures then arise. A comprehensive description of the thermodynamic and kinetic mechanisms that respectively drive these separate crystallization modes is provided. Finally, comparisons with experimental results reported in the literature highlight the promising potential of PF simulations to support the determination of process-structure relationships for improved PAL production.
CRIS-Team Scopus Importer:2023-12-15